Review on hardware-in-the-loop simulation of wave energy converters - Gaspar, J. F. (2022)
This paper presents a review of the state-of-the-art of the Hardware-In-The-Loop (HIL) technique applied to the development of wave energy converters (WEC) and power take-off systems (PTO). The presentation discusses existing frameworks and the technologies involved. In addition, a case study is discussed in order to exemplify the HIL concept applied to a WEC-PTO.